Signals of recent spatial expansions in the grey mouse lemur (Microcebus murinus) - Schneider, Nicole (BioMed Central, 2010)
BACKGROUND: Pleistocene events have shaped the phylogeography of many taxa worldwide. Their genetic signatures in tropical species have been much less explored than in those living in temperate regions. We analysed the genetic structure of a Malagasy primate species, a mouse lemur with a wide distribution (M. murinus), in order to investigate such phylogeographic processes on a large tropical island. We also evaluated the effects of anthropogenic pressures (fragmentation/deforestation) and natural features (geographic distance, rivers) on genetic structure in order to complement our understanding of past and present processes of genetic differentiation. RESULTS: The analysis of the mitochondrial D-loop sequences of 195 samples from 15 study sites (10 from a continuous forest and five from isolated forest fragments) from two adjacent Inter-River-Systems (IRSs) revealed that forest fragmentation and the river restrict gene flow, thereby leading to an increased genetic differentiation between populations beyond the effect of isolation-by-distance. Demographic simulations detected signals of two successive spatial expansions that could be preliminarily dated to the late Pleistocene and early Holocene. The haplotype network revealed geographic structure and showed deep molecular divergences within and between the IRSs that would be congruent with a two-step colonization scenario. CONCLUSIONS: This study supports the hypothesis of a relatively recent spatial expansion of the grey mouse lemur in northwestern Madagascar, which may also explain why this taxon, in contrast to its congeners, has not yet undergone allopatric speciation in the studied area and possibly across its presently wide range.